An efficient and thermostable soluble starch synthase in developing maize (Zea mays) grains - PANDEY, RAKESH; KUMARI, ANITA; PAUL, VIJAY; GHILDIYAL, M C (The Indian Journal of Agricultural Sciences, 2012)
High temperature during grain-filling stage is an important yield-limiting factor in wheat. It was reported earlier that a decrease in grain growth under high temperature is associated with a decrease in soluble starch synthase (SSS) activity, as this enzyme is extremely sensitive to high temperature. In attempt to identify thermostable SSS, a maize variety, in which grain development takes place under relatively warmer conditions, was compared with durum and aestivum wheat varieties in the present study. Maize was grown in rabi season so that grain development takes place in an increasing temperature as in wheat. The mean of maximum temperature during grain development period was highest for maize. In spite of such a high temperature exposure during grain development, the maize grains had a remarkably higher (3-4 times high) SSS activity as compared to wheat. Granule bound starch synthase (GBSS) activity was considerably lower than SSS activity, indicating SSS is the major enzyme for starch synthesis. High temperature exposure of excised developing grains showed no significant decrease in SSS activity in maize, whereas, T. aestivum var. Lok Bold showed a significant decrease. The present study reveals an efficient and relatively thermostable SSS in maize var. HQPM7 as compared to wheat, which could possibly be utilized in improving thermotolerance for grain growth in wheat.